Ethics and Equity Challenges in Telerehabilitation for Older Adults: Rapid Review - Mirella Veras; Louis-Pierre Auger; Jennifer Sigouin; Nahid Gheidari; Michelle LA Nelson; William C Miller; Anne Hudon; Dahlia Kairy (JMIR Aging)
Abstract BackgroundThe integration of technology in rehabilitation is transforming health care delivery for older adults, especially through telerehabilitation, which addresses barriers to in-person care. ObjectiveThis rapid review explores the ethical and equity concerns associated with telerehabilitation for older adults, focusing on challenges such as internet access, technology adoption, and digital literacy. MethodsConducted according to Cochrane Rapid Review guidelines, this review used the Metaverse Equitable Rehabilitation Therapy framework, focusing on equity and ethics. Studies included telerehabilitation services for adults aged 55 years and older, published between 2010 and 2023. Screening was conducted independently by 2 researchers using Rayyan (Qatar Computing Research Institute, Hamad Bin Khalifa University), with full-text review by additional team members. Searches were performed in Medline and CINAHL ResultsFrom 323 papers retrieved, 49 studies met the inclusion criteria. The included studies were published between 2013 and 2023. Disparities in socioeconomic status, geographic location, and racial and ethnic backgrounds were found to impact telerehabilitation use. Additionally, ethical concerns around privacy, security, and autonomy were often inadequately addressed. ConclusionsThis review emphasizes the need for culturally appropriate, accessible, and inclusive telerehabilitation services that integrate ethical and equity considerations into their design and delivery.